Bishop John Philip Saklil’s Theological Preference for The Indigenous Papuans: An Attempt to Respond to People's Doubts - Kira, Alfonsus Biru; Barril, Dante Salces (International Journal of Indonesian Philosophy & Theology, 2023)
This research explores and answers the question: What is Bishop John Philip Saklil's contribution to developing the Indigenous Papuans of the Timika Diocese Catholic Church? The church’s workers will use the answer to the question in making pastoral programs in their parish and responding to the people’s doubts about the church’s ministry and its preference for indigenous Papuans. This research was also made to increase people’s awareness of the problems in Papua and how important it is for us to give priority to Indigenous Papuans. The method used in this study is an analysis of two books related to Bishop Saklil: "The Church and Human Tragedy in Timika Diocese, Collection of Statements of Attitudes and Voices in the Mass Media" and "Mgr. John Philip Saklil, Pr, Founder of the Timika Diocese". Apart from that, the researcher, as a diocesan priest in Timika, directly observed the Bishop’s life from 2012-2019. This observation enriches the analysis of the two books mentioned above. Bishop Saklil's contribution to the support of the Papuans in Timika Diocese is Bishop Saklil's preference towards his ‘flocks’ who are Indigenous Papuans (Ind: Orang Asli Papua). There are two ways in which Bishop Saklil manifests his alignment with the Indigenous Papuans: First, by continuing to speak out against the injustice and incivility experienced by everyone in the land of Papua, particularly the Indigenous Papuans. Second, working in silence and continuing to struggle to tear down the building system creates unjust situations.